The Effect of Interactive Video-Based Learning Media on Motivation and Learning Outcomes of Junior High School Students - Santhy Naomi Jembormase; Leny Afia Lekahena; Benony Tamaela; Ahmad Husin (Ludi Litterarri, 2026)
Interactive video-based learning media has gained substantial attention as a pedagogical tool capable of enhancing student engagement, motivation, and academic achievement in secondary education. This study investigated the effect of interactive video-based learning media on the motivation and learning outcomes of junior high school students in Bandung, West Java, Indonesia. A quasi-experimental pre-test post-test design was employed with 120 Grade VIII students assigned to either an intervention group (n = 60) receiving structured interactive video media over eight weeks, or a control group (n = 60) receiving conventional instruction. Data were collected using a validated motivation scale (25 items, alpha = .81) and a curriculum-aligned achievement test (40 items, r = .79). Non-parametric Wilcoxon signed-rank and Mann-Whitney U tests confirmed statistically significant improvements in learning motivation (d = 0.72, p < .001) and learning outcomes (d = 0.69, p < .001) in the intervention group, with no significant changes observed in the control group. Multivariate regression identified interactive video use, frequency of viewing, and teacher facilitation as the strongest predictors of improvement. Findings affirm that purposefully designed interactive video media, when integrated within structured instructional frameworks, meaningfully enhances both affective and cognitive dimensions of junior high school student learning